South Africa : 2019 Article IV Consultation-Press Release; and Staff Report; and Statement by the Executive Director for South Africa. (IMF Staff Country Reports; Country Report ;, 2020)
This 2019 Article IV Consultation with South Africa discusses that subdued private investment and exports, and increased uncertainty have depressed growth and worsened social indicators. State-owned enterprises' (SOEs) risks are materializing, triggering government bailouts of Eskom and administrative intervention in other entities. High fiscal deficits have boosted debt. Nonresident investors are shedding equities and local currency bonds but showing appetite for foreign currency sovereign bonds amid supportive global financing conditions. The external position is moderately weaker than implied by fundamentals and desirable policies. Inflation has slowed to around the mid-point of the target band, aided by one-off factors, but inflation expectations are higher. Banks are sound, albeit with pockets of vulnerabilities. In the absence of fiscal space, a gradual and growth-friendly fiscal consolidation and increased spending efficiency are needed. The authorities should establish a credible debt anchor to stabilize debt in the medium term. Given the structural nature of the growth slowdown, the consolidation should be accompanied by reforms that reduce the cost of doing business and boost private investment.